Sodium and Potassium Intake from Food Diaries and 24-h Urine Collections from 7 Days in a Sample of Healthy Greek Adults - Athanasatou, Adelais; Kandyliari, Aikaterini; Malisova, Olga; Pepa, Alex; Kapsokefalou, Maria (Frontiers in Nutrition, 2018)
Objective The main objective of the present study was to evaluate sodium and potassium intake, employing 24 h and spot urine samples and food diaries for seven consecutive days. Methods For seven consecutive days subjects recorded their food and drink intakes, and recorded and collected all urinations. Food sodium and potassium intake were analyzed in 24- and 6-h intervals from wake-up time. Urine indices were analyzed in first morning, 24- and 6-h intervals samples over the day from wake-up time. The study took place in Agricultural University of Athens, Greece. In total, 163 healthy subjects (age 39 ± 12 years; 74 females) were enrolled in the study. Results Mean urine sodium excretion was 2,803.3 ± 1,249.0 mg/day (121.9 ± 54.3 mmol/day) and mean urine potassium excretion was 2,152.2 ± 913.3 mg/day (55.2 ± 23.4 mmol/day). The highest potassium concentration was measured in the afternoon, while the lowest sodium concentration was measured in the overnight 6-h interval. Food sodium intake was 1,983.2 ± 814.1 mg/day and food potassium was 2,264.5 ± 653.3 mg/day. The sources that contribute most in food sodium intake are dairy products 24%, breads 22%, and savory snacks 17%. Conclusion Strategies should encourage the Greek population to moderate sodium intake and promote potassium intake, thus adopting a healthier dietary and lifestyle pattern.